A low temperature approach for photo/cathodoluminescent Gd2O2S:Tb (GOS:Tb) nanophosphors. Issue 6 (21st December 2018) - Wang, Xuejiao; Meng, Qinghong; Li, Meiting; Wang, Xiaojun; Wang, Zhihao; Zhu, Qi; Li, Ji‐Guang
Abstract: Titrating the aqueous solution of equimolar RE(NO3 )3 and (NH4 )2 SO4 with NH4 OH to pH 9 at 4°C produced an amorphous precursor that yielded phase‐pure and well‐dispersed RE2 O2 S nanopowder (RE = Gd0.99 Tb0.01 ; GOS:Tb) via a RE2 O2 SO4 intermediate upon annealing in H2 . The powders calcined at the typical temperatures of 700/1200°C exhibited unimodal size distributions and have the average crystallize sizes of 17/55 nm, average particle sizes of 284/420 nm, and specific surface areas of 14.62/4.53 m 2 /g (equivalent particle sizes: 56/180 nm). The 1200°C product exhibited sharp green luminescence at 544 nm (FWHM = 2.3 nm; λ ex = 275 nm), with an absolute quantum yield of 24.8% and a fluorescence lifetime of 1.34 ms at room temperature. It was also shown that the powder possesses favorable thermal stability (the activation energy for thermal quenching of luminescence 0.305 eV) and is stable under electron beam irradiation up to 7 kV and 50 μA. The synthetic technique has the advantages of scalability and favorable dispersion and high chemical/phase purity for GOS powder, which may allow the sintering of scintillation ceramics at lower temperatures. Abstract : Gd2 O2 S:Tb nanophosphor with favorable dispersion and high chemical/phase purity was obtained via a low temperature precipitation approach.